Addressing Africa’s soil health challenges through the ten-year African Fertilizer and Soil Health Action Plan (2024-2034) and the longer-term Soil Initiative for Africa Framework - African Union Development Agency; Accelerating Impacts of CGIAR Climate Research for Africa (New Partnership for Africa’s Development, 2023)
Agricultural productivity in Africa is severely constrained by extensive land and soil degradation, a challenge that has persisted for decades. Approximately 75%-80% of the continent's cultivated area is reportedly degraded, resulting in a loss of 30kg-60kg of nutrients per hectare annually. This affects more than 485 million people (65% of the population)1. Further, projections indicate that over half of the currently arable land may become unusable by 2050. Various factors contribute to the continent's soil degradation, including the loss of organic matter, erosion from water and wind, acidification, biodiversity loss, and salinity.